Entrepreneurial Framing: A Literature Review and Future Research Directions. (May 2022) - Snihur, Yuliya; Thomas, Llewellyn D. W.; Garud, Raghu; Phillips, Nelson
There is increasing recognition among scholars that entrepreneurs use framing to legitimize their ventures and the broader fields within which they operate. Yet, there is no unifying framework to bring together existing theoretical perspectives on entrepreneurial framing and to make sense of their underlying mechanisms. Based on an integrative review of prior studies, we propose a conceptual framework for organizing this important literature. Our review also suggests directions for future research on entrepreneurial framing.